PENYALAHGUNAAN NARKOTIKA DAN ATURAN HUKUMNYA - Aryani, Esti (Universitas Slamet Riyadi, 2011)
Abstract: Narcotic crime is no longer done on an individual basis, but involves a lot of people are well organized with extensive networks and increasingly sophisticated modus operandi. Narcotic Act No. 35, 2009 was enacted to address the condition. Criminal investigation of narcotics and narcotics precursors made ​​by the police, and BNN investigators. Investigators can cooperate with each other in investigating drug crimes. Keywords: investigations, narcotics, narcotic precursors